The polymorphic locus rs1799945 of the HFE gene determines the risk of severe preeclampsia - Maria Yu. Abramova; Irina V. Ponomarenko; Valentina S. Orlova; Irina V. Batlutskaya; Olga A. Efremova; Mikhail I. Churnosov (IP Berlin A.V., 2023)
Background. Preeclampsia (PE) is a gestation complication that affects not only maternal and perinatal mortality but also the quality of life of women who have undergone PE, as well as their children in later life, which determines the urgency and relevance of the search for early markers of this complication of pregnancy, including genetic determinants. Aim. To evaluate the associations of GWAS-related hypertension candidate genes with the occurrence of severe PE. Materials and methods. All patients included in this study (217 females with severe PE and 498 females with physiological pregnancies) underwent a molecular genetic study of five GWAS-significant polymorphic loci of arterial hypertension candidate genes (rs1799945 HFE, rs805303 BAG6, rs4387287 OBFC1, rs633185 ARHGAP42, rs2681472 ATP2B1) and assessed the compliance of the empirical distribution of allelic variants and genotypes theoretically expected under HardyWeinberg law (at pbonf0.01). The associative search was performed using logistic regression analysis, and the odds ratio and its 95% confidence interval were calculated in PLINK v. 2.050. For polymorphisms that showed significant associations with severe PE, their regulatory effects were considered when using international projects on functional genomics (GTExportal, HaploReg (v4.1), PolyPhen-2). Results. The GG genotype of the rs1799945 polymorphic locus of the HFE gene is significantly associated with an increased risk of severe PE within the recessive genetic model (odds ratio 2.41; pperm=0.01). The polymorphism of rs1799945 of the HFE gene is localized in the histone markers H3K4me1 and H3K4me3 in pathogenetically significant organs and tissues for the development of PE, located in an evolutionarily conserved region located in the area of hypersensitivity to DNase-1. The rs1799945 locus of the HFE gene determines the missense mutation (aspartic acid replaces the amino acid histidine at position 63 in the Hereditary hemochromatosis protein) with the BENIGN predictor potential. Conclusion. The rs1799945 polymorphic locus of the HFE gene is associated with a high risk of severe PE.